Analisis K3 Mesin Bor Tangan pada Industri Fabrikasi PT. XYZ Menggunakan Metode HIRA - Indiyono, Lalak; Nurmawati, Nurmawati; Cahyono, Manggi Dwi; Andi, Dwi; Soejakti, Dahrijoso (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XYZ is one of the industries engaged in the fabrication sector with 20 workers. The small work location makes the production area full of machines and piles of scattered equipment that can cause danger to workers and the company. The absence of Occupational Safety and Health (K3) in the production process is very risky, so it can cause hazards and occupational diseases. This study aims to avoid and reduce the risk of work accidents that occur at PT. XYZ with work tools using hand drills by conducting risk analysis and control using the Hazard Identification and Risk Assessment (HIRA) method to identify hazards and assess risks. The results of this study are that work must be strictly guarded by HSE Officers, know the SOP, must use PPE so that safe, comfortable work is created, and production increases.